Juventude rural e processos educativos: um estudo de caso sobre as práticas de jovens em assentamentos rurais no Brejo Paraibano - Lima, Gisania Carla de (2021)
Young people live a time of being that is constituted with their experiences and with the understanding of the impacts of the changes that have been taking place over the last few years. The complexity, dilemmas and possibilities they find in certain social contexts are reflected in their experiences, making it essential to understand the contribution of this to practices that protect the achievement of autonomy with participation and dialogue. In this scenario, we highlight the implementation of educational processes of human, political and productive formation, which consider the plurality and diversity of youth in the countryside, as well as the recognition of the social condition of this generational group. In this thesis study, we analyze the contribution of young people's experiences in rural settlements of Brejo Paraibano in these processes for the development of practices of valorization and renewal of experiences in these territories, considering the construction of peasant identity and the trajectories of permanence traced. The theoretical-methodological framework adopted was based on the contributions of Minayo (1994, 1998), Stropasolas (2006), Groppo (2000, 2015, 2017), Abramoway (2015), Regina Novaes (2013), Calado (1994, 2007), Brandão (1980, 1985, 1986, 2002, 2013), Brandão and Streck (2006), Gohn (1992, 2005), Streck (2013), Streck and Zitkoski (2016), Geraldo Leão and Maria Isabel Antunes-Rocha (2015) , Elisa Guaraná de Castro (2005, 2015), Paulo Freire (1987, 1992, 1996), Edward Palmer Thompson (1981, 1998), among others, with which we understand youth as a social category, as a social actor in the rural context, their actions and projections based on educational processes, and the countryside as a space for relevant experiences for youth. Using the qualitative research approach, we opted for the case study method, taking as references Yin (2001), Goldenberg (1997), Stropasolas (2006). The methodological procedures adopted, such as survey and literature review, systematic monitoring, direct observation and application of interviews with a semi-structured script, were carried out to promote knowledge about the topic. The challenges encountered made us take a methodological stance to analyze the information presented in the statements of the research participants, going beyond what was presented as predictable and customarily said about youth, to find what young people create to add meaning to their trajectory. , launching itself to meet the unexpected, the unprecedented and viable. We identified that their educational experiences are related to the possibility of improving the quality of life in the countryside, because they contribute so that their participation makes sense, their dialogue is a motivating resource for relationships and knowledge is appropriated and transformed with their practices. The practices reveal particularities of these experiences, such as the connection of training processes with the principles of a liberating and emancipatory education; the promotion of a sense of belonging and affirmation for young people; and the existence of spaces for its performance. The experiences relate to their lives and become known and strengthened in public spaces and in groups. In this way, the knowledge built with this action has the merit of collaborating so that they are not disconnected from their reality, but that they can transform the relationships in the daily life of professional performance, production and sociability in the territories through dialogue and participation, providing hope for this youth.